Adaptation Level of Growth of Sengon (Paraserianthes Falcataria. L. Nielsen)) in Areas After Land Fire Sengonization in Bellabori Village, Parang Loe District Gowa District - Muchtar, Asikin; Magung, Agustinus; Herawaty; Wahyullah (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
This research aims to determine the level of adaptation to the growth of sengon (Paraserianthes falcataria) in the Sengonization Land Fire Ex-Fire Area in Belabori Village, Parang Loe District, Gowa Regency and to determine the security and protection system for Sengon (Paraserianthes falcataria) stands in the Sengonization Land Fire Ex-Fire Area in Belabori Village Parang Loe District, Gowa Regency. This research method is observation, namely making direct observations of research objects related to the problem being studied. This data was obtained through direct observation in the field, and direct observation of the objective conditions of this research location in Belabori Village, Parang Loe District, Gowa Regency, South Sulawesi. Primary data is data obtained from observations and recording of sengon tree species that are able to live on fire-affected land. The results of the research show that the growth adaptation level of Sengon (Paraserianthes falcataria L.Nielsen) after the fire in the Sengonisasi area, Bellabori Village, Parangloe District, Gowa Regency is very high, namely with an adaptation level of 87.27%, and the system for protecting and securing Sengon plants in the Sengonization location area Bellabori Village, Parangloe District, Gowa Regency is using a traditional protection system, namely by guarding the Guard Post, fencing the planting area with a living fence, and planting anti-fire plants from White Teak as a buffer zone from fire attacks, monitoring the perimeter of the planting area, and building a tower. fire in the corner of the area. Keywords: Growth, adaptation, sengon, fire scars